The Historical Development of the Results of the Iraqi National Team Participating in the Asian Cup Championships from 1972 to 2007 AD - Khalaf, Ali Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research is highlighted in studying and analyzing the results of the Iraqi teams participating in the Asian Cup tournaments, documenting and analyzing them, as well as documenting the number of matches, the names of the players and the matches that ended with the penalty shootout, the golden goal matches, the number of tournaments that the Iraqi team did not participate in, and the analysis of the reasons for not participating so that this research serves the wheel of progress and advancement Scientific in our beloved Iraq. As for the theoretical side, the researcher discussed a historical account of the football game in the civilization of the Mesopotamia Valley, as well as a historical account of the origins of football in the world, as the researcher discussed the establishment of the International Football Association in the World (FIFA), as well as a historical account of the origin of the game of football in Iraq. The researcher used the historical curriculum or the so-called documentary approach, benefiting from an analysis and discussion of the national team’s participation in the Asian Cup exclusively, and the researcher obtained the research results from the results of the Iraqi team in the Asian Cup qualifiers since 1972 until 2007, and the researcher came out with the most important findings, which are: Iraq’s participation since the start of the Asian Cup in 1956 and the first participation of Iraq in 1972 in the Thai championship until the Indonesia session in 2007 (6). There are breaks in the Asian Cup championship from 1980 until 1996. The political situation prevented Iraq from stopping the Asian Cup, as well as the wars and conflicts that prevented participation.